Requirement Engineering Analysis Based on Risk Assessment (Development of Management Information System for Domestic Wastewater in Gresik District) - M. A. Setiawan; R. V. H. Ginardi; I P. A. Wiguna (Institut Teknologi Sepuluh Nopember, 2019)
Public services and the provision of proper and sustainable sanitation infrastructure is one of the basic needs of the community, according to the 2030 Sustainable Development Goal (SDG's) and the 2015-2019 Medium-Term Development Plan (RPJMN), the Government of Indonesia has determined that by 2019 achieving 100% Universal Access in the sanitation sub-sector service in order to accelerate infrastructure development to encourage economic growth and equity. This emphasizes the importance of optimizing water supply and sanitation services and especially the domestic wastewater sector. In the implementation of these services the operator operators often experience obstacles in integrating all business processes due to the limitations of the management system they have. The purpose of this study was to analyze the requirements engineering process with risk analysis and then integrate the system with the concept of enterprise resource planning with a case study of the development of a domestic wastewater management information system in the Public Works and Spatial Planning Office of Gresik Regency. This study uses the stages of preparing Requirements Engineering documents in accordance with ISO / IEC / IEEE 29148-2011 standards and Risk Assessment Analysis with ISO 31000 standards. Software Requirement Specifications (SRS) are then used as a reference in developing systems with an Enterprise Resource Planning (ERP) approach. The results of this study produced 20 risk variables that are relevant with 5 variables included in the high category, 6 variables included in the medium category and the remaining 9 variables included in the low category. Lack of stability, availability, scalability, usability, security, extensibility is one of the risk variables that are categorized as high. Ensuring the merger of all SRS modules to function properly is an action that can be carried out from the results of risk mitigation and becomes a consideration in the incorporation of 9 SRS modules using the Enterprise Resource Planning method